The impact of soluble HLA-G in IVF/ICSI embryo culture medium on implantation success - Radwan, Paweł; Tarnowska, Agnieszka; Piekarska, Karolina; Wiśniewski, Andrzej; Krasiński, Rafał; Radwan, Michał; Nowak, Izabela (Frontiers in Immunology, 2022)
The HLA-G molecule is widely accepted as an important factor for pregnancy success. Its expression has been detected in the extravillous trophoblasts. Soluble HLA-G (sHLA-G) was found in the genital tract, pre-implanted embryos as well as in seminal fluid. In this study, we investigated the concentration of sHLA-G (sHLA-G1 and sHLA-G5) in media from 344 single cultured embryos following in vitro fertilization/intracytoplasmic sperm injection (IVF/ICSI). The level of sHLA-G (IU/ml) was tested with a sandwich enzyme-linked immunosorbent assay (ELISA) kit. We correlated sHLA-G secretion with ovarian stimulation protocols, the type of embryo transfer (fresh or frozen cycle) and the quality of the embryos. The ovarian stimulation protocol affects the secretion of sHLA-G by the embryo. Embryos obtained from the long agonist protocol secreted more sHLA-G than those originating from the short antagonist protocol (p = 0.0001). Embryos whose transfer resulted in a clinical pregnancy and/or live birth secreted more sHLA-G compared to those whose transfer ended without pregnancy. This was particularly observable in embryos following the long ovarian stimulation protocol and from a frozen embryo cycle. In conclusion, sHLA-G secreted by the embryo has an impact on implantation and live birth and could be a developmental potential marker of the embryo. Its concentration depends on the ovarian stimulation protocol used.